In search of an elusive Antarctic circumpolar wave in sea ice extents: 1978–1996 - Gloersen, Per; Huang, Norden E. (Polar Research, 1999)
For ease in discerning an Antarctic circumpolar wave in the perimeter of the ice pack, we construct a time series of the sea ice extents (essentially the area within the ice perimeter) in 1-degree longitudinal sectors for the period 1978-1996, as observed with the multichannel microwave imagers on board the NASA Nimbus 7 and the DOD (Dept. of Defense) DMSP (Defense Meteorological Satellite Program) F8, F11, and F13 satellites. After converting the time series into complex numbers by means of a Hilbert transform, we decompose the time series of the 360 sectors into its complex principal components (CPCs), effectively separating the spatial and temporal values. Then we decompose the real and imaginary parts of the temporal portions of the first three CPCs (complex principal compenents) by Empirical Mode Decomposition into their intrinsic modes, each representing a narrow frequency band, resulting in a collection of three CPCs for each intrinsic mode. Finally, we reconstruct the data in two different ways. First, we low-pass filter the data by combining all of the intrinsic modes of each CPC with periods longer than two years, which we designate as lowpass filtered. Next, we select the intrinsic mode of each CPC with periods of approximately four years, which we designate the quasiquadrennial (QQ) modes. The low-pass filtered time series shows eastward propagating azimuthal motion in the Ross and Weddell Seas, but no clearly circumpolar motion. The QQ time series, on the other hand, clearly shows eastward propagating circumpolar waves, but with occasional retrograde motion to the west.
Keywords: Rosshavet; Sørishavet; Weddellhavet; havis; klimatologi; meteorologi; oseanografi

Experimental formation of sea ice: importance of water circulation and wave action for incorporation of phytoplankton and bacteria - Weissenberger, Jürgen; Grossmann, Sönnke (Polar Biology, 1998)
The efficiency of physical concentration mechanisms for enrichment of algae and bacteria in newly formed sea-ice was investigated under defined conditions in the laboratory. Sea-ice formation was simulated in a 3,000 l tank under different patterns of water movement. When ice formed in an artificially generated current pattern, algal cells were substantially enriched within the ice matrix. Enrichment factors for chlorophyll a calculated from the ratio between the concentrations in ice and underlying water reached values of up to 53. Repeated mixing of ice crystals into the water column, as well as flow of water through the new ice layer, contributed to the enrichment of algae in the ice. Wave action during ice formation revealed lower phytoplankton enrichment factors of up to 9. Mixing of floating ice crystals with underlying water and pumping of water into the ice matrix by periodical expansion and compression of the slush ice layer were responsible for the wave-induced enrichment of algal cells. Physical enrichment of bacteria within the ice was negligible. Bacterial biomass within new ice was enhanced only when the concentration of algae was high. At low algal biomass, bacteria experienced substantial losses in the ice, most likely due to brine drainage, which were not observed for the microalgae. Bacterial cells are therefore not scavenged by ice crystals and the observed enrichment and sustainment of bacterial biomass within newly formed ice depend on their attachment to cells or aggregates of algae. Division rates of bacteria changed only slightly during ice formation.
Keywords: Sørishavet; Weddellhavet; alger; bakterier; fytoplankton; havis; marin biologi; polarområdene

Analysis of merged SMMR-SSMI time series of Arctic and Antarctic sea ice parameters 1978–1995 - Bjørgo, Einar; Johannessen, Ola M.; Miles, Martin W. (Geophysical Research Letters, 1997)
The most consistent means of investigating the global sea ice cover is by satellite passive microwave sensors, as these are independent of illumination and cloud cover. The Nimbus 7 Scanning Multichannel Microwave Radiometer (SMMR) and the Defense Meteorological Satellite Program (DMSP) Special Sensor Microwave Imager (SSMI) provide information on the global sea ice cover from 1978 to present. The two instruments flew simultaneously during a 6-week overlap period in July and August 1987, thus enabling intercomparison of the two sensors. Brightness temperatures are corrected for instrument drift and calibration differences in order to produce continuous time series of monthly averaged Arctic and Antarctic sea ice extent and sea ice area through the use of the NOrwegian Remote Sensing EXperiment (NORSEX) algorithm, which relates brightness temperatures to ice concentration. Statistical analysis on the time series estimates the decreases in Arctic ice extent and ice area to be 4.5% and 5.7%, respectively, during the 16.8-year observation period. The overall trends established here serve to better define and strengthen earlier assertions of a reduced ice cover, based on analysis of SMMR and SSMI data taken separately. These results are consistent with GCM simulations that suggest retreat of the sea ice cover under global warming scenarios.
Keywords: Antarktis; global oppvarming; havis; klimaendringer; meteorologi; polarområdene; satellite mikrobølgesensorer

Sea ice projects during NARE 1992/93 - Løyning, Terje Brinck; Vinje, Torgny (Report of the Norwegian Antarctic Research Expedition 1992/93, 1997)
Keywords: NARE 1992/93; Sørishavet; Weddellhavet; havis; sjøis

Synedropsis gen. nov., a genus of araphid diatoms associated with sea ice - Hasle, Grethe Rytter; Medlin, Linda K.; Syvertsen, Erik E. (Phycologia, 1994)
A new araphid diatom genus, Synedropsis Hasle, Medlin et Syvertsen, is described from sea ice. The generitype, Synedropsis hyperborea (Grunow) Hasle, Medlin et Syvertsen from the Arctic, was first described as a species of Synedra, as was the antarctic Synedropsis fragilis (Manguin) Hasle, Syvertsen et Medlin. A second antarctic species of Synedropsis is a new combination of Cymatosira laevis Heiden in Heiden & Kolbe. In addition four new taxa, S. hyperboreoides Hasle, Syvertsen et Medlin, S. recta Hasle, Medlin et Syvertsen, S. lata Hasle, Medlin et Syvertsen and S. lata var. angustata Hasle, Medlin et Syvertsen are described from the Antarctic. The valve wall is laminar with uniseriate, often poorly developed striae and a wide sternum. Each valve possesses apical fields composed of slits. A labiate process is positioned near one apical slit field. The valve outline for most species exhibits considerable stadial variation. The girdle has several bands, most with one row of poroids close to the pars interior. Thus Synedropsis is closely related to the marine Fragilaria striatula Lyngbye except in the structure of the apical fields and the number of bands. Species observed in uncleaned material appeared in stellate or, more seldom, ribbon-shaped colonies. Synedropsis hyperborea is a common epiphyte on the ice-associated Melosira arctica Dickie in the Arctic. The antarctic species were found mainly in the bottom ice community, S. fragilis as an epiphyte on other diatoms.
Keywords: Rosshavet; Sørishavet; Weddellhavet; botanikk; diatomeer; havis; kiselalger; marin biologi; plankton

Phytoplankton distribution in relation to sea ice, hydrography and nutrients in the northwestern Weddell Sea in early spring 1988 during EPOS - Bianchi, Franco; Boldrin, Alfredo; Cioce, F; Dieckmann, Gerhard Stephan; Kuosa, Harri; Larsson, A M; Nöthig, Eva-Maria; Sehlstedt, P I; Socal, Giorgio; Syvertsen, Erik E (Polar Biology, 1992)
Phytoplankton biomass and distribution of major phytoplankton groups were investigated in relation to sea ice conditions, hydrography and nutrients along three north-south transects in the north western Weddell Sea in early spring 1988 during the EPOS Study (European Polarstern Study), Leg 1. Three different zones along the transects could be distinguished: 1) the Open Water Zone (OWZ) from 58-degrees to 60-degrees-S with high chlorophyll a concentrations up to 3.5-mu-g l-1; 2) the Marginal Ice Zone (MIZ) from 60-degrees to about 62.5-degrees with chlorophyll a concentrations between 0.1 and 0.3-mu-g l-1, and 3) the closed pack-ice zone (CPI) from 62.5-degrees to 63.2-degrees-S with chlorophyll a concentrations below 0.1-mu-g l-1. Nutrient concentrations increased towards the south showing winter values under the closed pack-ice. Centric diatoms such as Thalassiosira gravida and Chaetoceros neglectum forming large colonies dominated the phytoplankton assemblage in terms of biomass in open water together with large, long chain forming, pennate diatoms, whereas small pennate diatoms such as Nitzschia spp., and nanoflagellates prevailed in ice covered areas. Fairly low concentrations of phytoplankton cells were encountered at the southernmost stations and many empty diatom frustules were found in the samples. The enhanced phytoplankton biomass in the Weddell-Scotia-Confluence area is achieved through sea ice melting in the frontal zone of two different water masses, the Weddell and the Scotia Sea surface waters.
Keywords: Sørishavet; Weddellhavet; biomasse; diatomeer; fytoplankton; havis; hydrografi; marin biologi; oseanografi

Ecology of sea ice biota. 1. Habitat, terminology, and methodology - Horner, Rita; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjorn; Hoshiai, Takao; Legendre, Louis; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
Polar regions are covered by extensive sea ice that is inhabited by a variety of plants and animals. The environments where the organisms live vary depending on the structure and age of the ice. Many terms have been used to describe the habitats and the organisms. We here characterize the habitats and communities and suggest some standard terms for them. We also suggest routine sampling methods and reporting units for measurements of biological and chemical variables.
Keywords: Sørishavet; biodiversitet; havis; marin biologi; polarområdene; økologi

Ecology of sea ice biota. 2. Global significance - Legendre, Louis; Ackley, Stephen F.; Dieckmann, Gerhard S.; Gulliksen, Bjørn; Horner, Rita; Hoshiai, Takao; Melnikov, Igor A.; Reeburgh, William S.; Spindler, Michael; Sullivan, Cornelius W. (Polar Biology, 1992)
The sea ice does not only determine the ecology of ice biota, but it also influences the pelagic systems under the ice cover and at ice edges. In this paper, new estimates of Arctic and Antarctic production of biogenic carbon are derived, and differences as well as similarities between the two oceans are examined. In ice-covered seas, high algal concentrations (blooms) occur in association with several types of conditions. Blooms often lead to high sedimentation of intact cells and faecal pellets. In addition to ice-related blooms, there is progressive accumulation of organic matter in Arctic multi-year ice, whose fate may potentially be similar to that of blooms. A fraction of the carbon fixed by microalgae that grow in sea ice or in relation to it is exported out of the production zone. This includes particulate material sinking out of the euphotic zone, and also material passed on to the food web. Pathways through which ice algal production does reach various components of the pelagic and benthic food webs, and through them such top predators as marine mammals and birds, are discussed. Concerning global climate change and biogeochemical fluxes of carbon, not all export pathways from the euphotic zone result in the sequestration of carbon for periods of hundreds of years or more. This is because various processes, that take place in both the ice and the water column, contribute to mineralize organic carbon into CO2 before it becomes sequestered. Processes that favour the production and accumulation of biogenic carbon as well as its export to deep waters and sequestration are discussed, together with those that influence mineralization in the upper ice-covered ocean.
Keywords: Sørishavet; biodiversitet; biogeokjemi; havis; karbondioksid; klimaendringer; marin biologi; polarområdene; økologi

The ecophysiology of under-ice fauna - Aarset, Arne V (Polar Research, 1991)
Keywords: Antarktis; amfipoder; fauna; havis; polarområdene; sjøis; zoologi; økofysiologi

Microbial communities from the sea ice and adjacent water column at the time of ice melting in the northwestern part of the Weddell Sea - Mathot, Sylvie; Becquevort, Sylvie; Lancelot, Christiane (Polar Research, 1991)
Keywords: Sørishavet; Weddellhavet; alger; bakterier; diatomeer; havis; mikrobiologi; protozo; sjøis; smelting

Virkninger av klimaendringer i polarområdene : bidrag til den interdepartementale klimautredningen - Kverndal, Arnt-Ivar; Elvebakk, Arve; Jaworowski, Zbygniew; Hansson, Rasmus (Norsk Polarinstitutt, 1990)
Keywords: Antarktis; biologi; drivhuseffekten; dyreliv; fiskeri; flora; havbruksnæring; havis; havnivå; isbreer; klimaendringer; klimagasser; permafrost; planter; polarområdene; vannressurser; økologi